Emergence of topological Mott insulators in proximity of quadratic band touching points - Mandal, I.; Gemsheim, S. (Condensed Matter Physics, 2019)
Recently, the field of strongly correlated electrons has begun an intense search for a correlation induced topological insulating phase. An example is the quadratic band touching point which arises in a checkerboard lattice at half-filling, and in the presence of interactions gives rise to topological Mott insulators. In this work, we perform a mean-field theory computation to show that such a system shows instability to topological insulating phases even away from half-filling (chemical potential µ = 0). The interaction parameters consist of on-site repulsion (U), nearest-neighbour repulsion (V), and a next-nearest-neighbour correlated hopping (tc). The tc interaction originates from strong Coulomb repulsion. By tuning the values of these parameters, we obtain a desired topological phase that spans the area around (V = 0, µ = 0), extending to regions with (V > 0, µ = 0) and (V > 0, µ > 0). This extends the realm of current experimental efforts to find these topological phases.